Missed opportunities: Confiscation of weapons in domestic violence cases - Smythe, Dee (2016)
Part of a series in the SA Crime Quarterly on the implementation of the Domestic Violence Act, this article focuses on the use of weapons in incidents of domestic violence as reflected in applications for protection orders at three Western Cape jurisdictions. Weapons are often used in domestic violence. If the police and magistrates use the powers available to them to seize weapons, it will go a long way to protecting women and the broader public